Dysphagia lusoria in a young woman with chest pain. Issue 6 (2nd November 2022) - Songtanin, Busara; Jacob, Roy; Mittal, Neha
Abstract: Patients with dysphagia often have an esophageal disorder. This case report describes a patient with persistent dysphagia and chest pain who had a normal esophagogastroduodenoscopy. Computed tomography of the chest with contrast revealed an aberrant right subclavian artery compressing the esophagus. A vascular procedure was performed and corrected the dysphagia. This case demonstrates that aberrant vessels can occasionally cause dysphagia.